Efforts to Prevent Radicalism through Studying the Book of Mafahim Yajibu An-Tushohhah at the Darul Muqorrobin Kendal Islamic Boarding School, Central Java, Indonesia - Alaydrus, M. Zidane Yusva; Murtadho, Ali; Syafiq, Muhammad Azmi (Analisis: Jurnal Studi Keislaman, 2024)
Radicalism is a serious threat that has a broad impact on social order, security and societal stability. Acts of radicalism are often associated with violence and intolerance towards differences of opinion and belief, which can trigger social conflict and threaten the values of diversity and unity of the country. Therefore, effective preventive efforts are very necessary to overcome radicalism, especially among the younger generation. This study focuses on the Darul Muqorrobin Kendal Islamic Boarding School, Central Java, and investigates efforts to prevent radicalism among students through a study of the book Mafahim Yajibu An-Tushohhah. This research uses a descriptive qualitative approach that is exploratory and evaluative. Primary and secondary data were obtained through literature reviews, documentation studies, interviews and observations. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The research results show that the book Mafahim Yajibu An-Tushohhah plays an important role in preventing the spread of radicalism among students at the Darul Muqorrobin Islamic Boarding School, Kendal, Central Java. This book provides a comprehensive understanding of moderate Islamic teachings, which significantly protects students from the influence of radical ideology.